Epidemiology of rotavirus infection in Thailand - Maneekarn N. (2014)
Rotavirus is a major cause of acute severe diarrhea in children worldwide and an important cause of death among young children in developing countries. Group A rotaviruses are antigenically complex and multiple serotypes infect humans. Reassortant rotavirus vaccines are now available which offer protection against severe illness caused by rotavirus serotypes G1-4. Before vaccines are introduced into target populations, it is necessary to establish the baseline data of the epidemiology of rotavirus infection in those countries. The purpose of the present study is to provide information related to the epidemiology of rotavirus infection in Thailand. All rotavirus studies performed in Thailand were found through Medline and Thai Index Medicus searches. A total of 26 of the most relevant studies published in international and national journals are reviewed. Most studies reported that the prevalence of rotavirus infection in Thailand was 27-34%, although a few studies have reported a prevalence above this range. The peak seasonal distribution of rotavirus infection among children hospitalized with diarrhea in Thailand was seen in the dry cool seasons: October to February. The prevalence of rotavirus infection was most frequently found in children aged 6-11 months up to 2 years. G1 was the most prevalent serotype in Thailand, followed by G2, G4 and G3, respectively. At least three G serotypes, mostly G1, G2 and G4, are seen to coexist in Thailand each epidemic year and in some studies all four G-serotypes were reported in the same epidemics. In a 1996-1997 study, G9 was the third prevailing serotype after G1 and G2, respectively. These results indicate that rotavirus epidemics occur in Thailand every year and children are the most affected population. In Thailand, although G1-G4 have been reported, G1 is the most prevalent serotype in each epidemic and G9 is becoming increasingly common.